Ein System von Lösungen einer Klasse linearen Gleichungen mit partiellen Arbleitungen - Kisielius, J. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. В. Киселюс. Система решений одного класса линейных уравнений с частными производнымиJ. Kisielius. Vienos tiesinių lygčių su dalinėmis išvestinėmis klasės sprendinių sistema